PENGARUH SHARIA COMPLIANCE, ISLAMIC CORPORATE GOVERNANCE, CAR, DAN ZAKAT TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH: Dibuat oleh Ayu Khumala Sari, Fadli Hudaya, Sobrotul Imtikhanah (Prodi Ekonomi Syariah FEB Universitas Muhammadiyah Pekajangan Pekalongan) - Fadli Hudaya; Ayu Kumalasari; Sobrotul Imtikhanah (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2020)
This study aimed to examine the effect of Sharia Compliance, Islamic Corporate Governance, Capital Adequacy Ratio and zakat on financial performance at Islamic Commercial Banks. The independent variable used was Sharia Compliance, proxied by Islamic Income Ratio, Profit Sharing Ratio, Islamic Investment Ratio, Islamic Corporate Governance, Capital Adequacy Ratio and zakat. The dependent variable used in this study was financial performance as proxied by Return On Assset (ROA) in Islamic Commercial Banks. This research was a quantitative study using SPSS version 21 and Microsoft Excel. This study used a population of 14 Islamic commercial banks in Indonesia in 2015-2018, so that the total sample is 32. The data analysis technique used in this study was multiple linear regression analysis. Based on the result of this study, the Islamic Income Ratio, Profit Sharing Ratio, Islamic Investment Ratio, Islamic Corporate Governance, Capital Adequacy Ratio and zakat simultaneously affected the financial performance of Islamic Commercial Banks. Partial testing showed that the Islamic Income Ratio and Profit Sharing Ratio had a significant effect on the financial performance of Islamic Commercial Banks. Meanwhile, Islamic Investment Ratio, Islamic Corporate Governance, Capital Adequacy Ratio and zakat did not affect the financial performance of Islamic Commercial Banks. Keywords: Sharia Compliance, Islamic Income Ratio, Profit Sharing Ratio, Islamic Investment Ratio, Islamic Corporate Governance, CAR, Zakat, ROA, Islamic Bank.